2006
DOI: 10.1093/cercor/bhl140
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cortical Expression of Two Synaptogenic Thrombospondins in Human Brain Evolution

Abstract: Thrombospondins are extracellular-matrix glycoproteins implicated in the control of synaptogenesis and neurite growth. Previous microarray studies suggested that one gene of this family, thrombospondin 4 (THBS4), was upregulated during human brain evolution. Using independent techniques to examine thrombospondin expression patterns in adult brain samples, we report approximately 6-fold and approximately 2-fold greater expression of THBS4 and THBS2 messenger RNA (mRNA), respectively, in human cerebral cortex co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 46 publications
5
69
0
Order By: Relevance
“…S2C). Similarly, thrombospondin 4 (THBS4), previously shown to be associated with synaptic functions and synapse formation (Caceres et al 2003(Caceres et al , 2007, also shows significantly higher expression in the human PFC compared with PFCs of the other two species throughout adulthood. This implies that humans might sustain higher levels of synaptogenesis or synaptic activity throughout adult life.…”
Section: Discussionmentioning
confidence: 98%
“…S2C). Similarly, thrombospondin 4 (THBS4), previously shown to be associated with synaptic functions and synapse formation (Caceres et al 2003(Caceres et al , 2007, also shows significantly higher expression in the human PFC compared with PFCs of the other two species throughout adulthood. This implies that humans might sustain higher levels of synaptogenesis or synaptic activity throughout adult life.…”
Section: Discussionmentioning
confidence: 98%
“…However, the clear differences in behavioral and cognitive development between enculturated apes and humans point to particular neural specializations that make the human brain-but not the brain of great apes-extremely responsive to exogenous influences. In this light, several comparative studies have shown molecular and microstructural specializations in the human brain indicating an increased level of synaptic plasticity (21,22), which might be linked to increased learning abilities.…”
mentioning
confidence: 98%
“…This interpretation is supported by evidence that the cortical regions that develop later in human ontogeny also underwent the greatest expansion during human brain evolution (18,19), suggesting that evolutionary selection to enlarge these regions was accompanied by a prolongation of their development. Among these regions, the prefrontal cortex, which shows particularly extended maturation in humans relative to macaques, has also been reported to exhibit uniquely human neuroanatomical and molecular specializations (20)(21)(22)(23)(24)(25). However, because macaques and humans shared a last common ancestor ∼25 million y ago, it is currently unclear whether features that distinguish human cortical development (i.e., extended period of synaptogenesis and maturational delay of prefrontal pyramidal neurons) are unique to our lineage, or if they evolved before the divergence of modern humans and more closely related great ape species, such as chimpanzees.…”
mentioning
confidence: 99%